The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fpls.2013.00359
|View full text |Cite
|
Sign up to set email alerts
|

Iron: an essential micronutrient for the legume-rhizobium symbiosis

Abstract: Legumes, which develop a symbiosis with nitrogen-fixing bacteria, have an increased demand for iron. Iron is required for the synthesis of iron-containing proteins in the host, including the highly abundant leghemoglobin, and in bacteroids for nitrogenase and cytochromes of the electron transport chain. Deficiencies in iron can affect initiation and development of the nodule. Within root cells, iron is chelated with organic acids such as citrate and nicotianamine and distributed to other parts of the plant. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
166
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(177 citation statements)
references
References 113 publications
2
166
0
4
Order By: Relevance
“…Glyma09g31910 and Glyma08g04830 are in a clade of the PLAC8 family, known as plant cadmium resistance (PCR) proteins and fruit weight 2.2-like (FWL). Of particular interest, given the requirement for metal transport into the symbiosome (132,133), is the reported role of two members of this clade from Arabidopsis, AtPCR1 and AtPCR2, that appear to be involved in the export of heavy metals from root cells (134,135). This would translate to an import of metal into the symbiosome and the presence of homologous proteins on the SM suggests a possible role in maintaining adequate nutrition for the isolated bacteroids through import of a variety of metal cations.…”
Section: Soybean Symbiosome Proteomementioning
confidence: 99%
“…Glyma09g31910 and Glyma08g04830 are in a clade of the PLAC8 family, known as plant cadmium resistance (PCR) proteins and fruit weight 2.2-like (FWL). Of particular interest, given the requirement for metal transport into the symbiosome (132,133), is the reported role of two members of this clade from Arabidopsis, AtPCR1 and AtPCR2, that appear to be involved in the export of heavy metals from root cells (134,135). This would translate to an import of metal into the symbiosome and the presence of homologous proteins on the SM suggests a possible role in maintaining adequate nutrition for the isolated bacteroids through import of a variety of metal cations.…”
Section: Soybean Symbiosome Proteomementioning
confidence: 99%
“…Two of these genes were of unknown function and one (Glyma10g31610) was a yellow stripelike (YSL) ortholog (Table 3). YSLs are membrane located transporters that are important to the intercellular transport of iron and other metals and contribute to the overall metal nutrition in plants (Brear et al 2013;Conte et al 2013). Although metal ion transporters have not been analyzed in detail in plant-aphid interactions, it is possible that they could be part of the cascade of changes that are elicited upon aphid feeding (Boyd 2006;Poschenrieder et al 2006).…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…NRAMP3 and VIT1 have contrasting functions: while the first is responsible for the remobilization from the vacuole (Lanquar et al, 2005), the second is responsible for the Fe loading in the vacuole (Kim et al, 2006). Studies in A. thaliana demonstrate that NRAMP3 is an H + metal symporter responsible for Fe and Mn remobilization from the vacuole, a crucial step during early seedling development (Lanquar et al, 2010 (Brear et al, 2013). Studies in A. thaliana (Kim and Guerinot, 2007) demonstrated that AtNRAMP3 and AtVIT1 mutants present arrested seedling growth when grown on Fe deficient soils.…”
Section: Resultsmentioning
confidence: 99%
“…Fe 2+ is then transported into the plant by specific membrane transporters (Grotz and Guerinot, 2006), such as the Iron-Regulated Transporter 1 (IRT1) (Waters et al, 2002). A broad spectrum of transporters have been characterized, such as the Natural Resistance Associated Macrophage (NRAMP) proteins, involved in Fe import into the cytoplasm, the Vacuolar Iron Transporter (VIT), involved in the uptake of Fe 2+ into the vacuole for storage (Brear et al, 2013), and the Yellow Stripe 1-Like (YSL), involved in the transport of Fe 2+ -NA complexes (Kim et al, 2006). Free Fe is toxic since it facilitates the generation of highly reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%